Effects of strength training on fatigue and performance in elite athlete - A brief review - Spencer, N. D. (Journal of Australian Strength and Conditioning, 2016)
Strength training is a critical component of athletic programming and while fatigue is an expected result from any form of training, current fatigue models examine the acute effects of strength training on central and peripheral fatigue with more recent evidence highlighting the effects of strength training on the hormonal profile of athletes. In September 2014 a literature strategy was conducted using Cochrane, MEDLINE, CINHAL, EMBASE and SPORTDiscus and the terms `resistance training`, `strength training`, `fatigue`, `performance`, `athlete`, `central fatigue`, `peripheral fatigue`, `hormone` and `exertion` searched. The aim of this review was to examine current literature and the implications of strength training on the hormonal, metabolic and neuromuscular components of fatigue while provide suggestions for practical application and considerations for strength coaches. To the best of this author`s knowledge, there remains a general lack of guidance for coaches when examining the overall effect of strength training on accumulative fatigue. Based on the literature presented within this review, strength coaches should use countermovement jump scores as a primary measure of neuromuscular fatigue with scores of one standard deviation away from the mean considered significant. Hormonal responses to strength training indicate highly trained athletes respond better to periods of high intensity training than their lesser trainer counterparts with a testosterone to cortisol ratio of 0.30 x 10-3 considered to indicate a catabolic state indicating risk of fatigue. However its practical use is not widely supported.